MENGUAK PRODUKTIVITAS KERJA KARYAWAN HOTEL DI MAKASSAR - Mustafa Hasbar (AkMen JURNAL ILMIAH, 2012)
The research was conducted for employee productivity mengetahaui Hotel "P" Makassar. This study is a research experiment, which will examine the influence of working conditions and communication of employee productivity, with the technique of descriptive analysis and multiple linear regression. The results showed that the variable working conditions (X1) and communication (X2) significant effect on work productivity. This is indicated by the value t count for the variables X1, X2 is greater than t table value (7.027; 8.588;> 1.679). Communication (X2) has the most dominant influence on the assessment of work productivity (Y). It is shown from communication regression coefficient value (X2) is greater than the value of the regression coefficient of variable working conditions (0.958> 0.701). Taken together (simultaneous) variable working conditions (X1) and communication (X2) jointly affect labor productivity (Y). It is shown from the calculated F value (38.872) is greater than the table F value (2.807). Sedangka coefficient of determination (R2) proved that the labor productivity (Y) of 0.623 or 62.3% influenced by variables working conditions (XO and communication (X2) and the remaining 0.377 or 37.7% influenced by other variables outside of the study, such as motivation, social welfare, leadership and others.